Skala Karakter Religius Siswa SMA Implementasi Nilai Utama Karakter Kemendikbud - Saputra, Nofrans Eka; Ekawati, Yun Nina; Islamiah, Rahmadhani (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2020)
AbstractConflicts and disputes related to religion, race, and also ethnic groups, as well as the hedonism and egoism of Indonesian people today, are eroding the religious and national character of the nation. The Government of Indonesia, through the Ministry of Education and Culture, seeks to strengthen character education (PPK) as a way to grow, instill, and strengthen the positive character of the nation's children. This study aims to make scale the religious character of high school students based on the values of the main characters of the Ministry of Education and Culture by using the principal component analysis (PCA) technique. The population of this research is high school students in Jambi Province with 337 high school students with ages range 15 to 18 years. the sampling technique using purposive sampling. The results of the analysis through the Principal Component Analysis method with orthogonal rotation and varimax extraction resulted in six principal components that were successfully reduced, namely: components of peace, tolerance, protection, detachment, respect and friendship. Each component has a coefficient of 0,000 which means that each component measures a different aspect, each aspect independent of each other and not related to each other. The reliability test using the Guttman Method yields a value of λ = 0.781 which means the scale has a degree of reliability sufficient to measure the religious character of High School Students and can be used with other measurements to support validation of the measurement.AbstrakBerbagai konflik dan perselisihan terkait perbedaan agama, ras, serta etnis bangsa maupun perilaku hedonisme dan egoisme masyarakat Indonesia saat ini mengindikasikan terkikisnya karakter religius dan pansilais bangsa. Pemerintah Indonesia melalui Kemdikbud mengupayakan penguatan pendidikan karakter (PPK) sebagai cara untuk menumbuhkan, menanamkan, dan menguatkan kembali karakter positif pada anak bangsa. Penelitian ini bertujuan untuk membuat skala karakter religius siswa SMA yang didasarkan pada nilai-nilai utama karakter Kemdikbud dengan menggunakan teknik principal component analysis (PCA). Populasi penelitian ini adalah siswa Sekolah Menengah Atas (SMA) di Provinsi Jambi dengan responden sebanyak 337 siswa SMA yang berusia 15 sampai 18 tahun. teknik pengambilan sampel dengan purposive sampling.Hasil analisis melalui metode Principal Component Analssis dengan rotasi orthogonal dan ekstraksi varimaks menghasilkan enam komponen yang berhasil direduksi, yaitu: komponen cinta damai, toleransi, perlindungan, teguh pendirian, hormat dan persahabatan. Setiap komponen memiliki koefisien korelasi 0.000 yang berarti setiap komponen mengukur aspek yang berbeda, berdiri sendiri dan tidak saling berhubungan satu sama lain. Uji reliabilitas dengan Metode Guttman menghasilkan nilai λ=0.781 yang berarti skala memiliki derajat keterpercayaan yang cukup untuk mengukur karakter religius dan dapat digunakan dengan pengukuran lain untuk mendukung validasi pengukuran.